2022
DOI: 10.3897/bdj.10.e83117
|View full text |Cite
|
Sign up to set email alerts
|

Formerly considered rare, the ant species Cryptopone ochracea (Mayr, 1855) can be commonly detected using citizen-science tools

Abstract: Citizen science is a valuable tool for monitoring different species, especially in cases concerning truly rare and difficult-to-detect species where time-consuming field studies are limited and long-term research projects are uncertain. To better understand the distribution of the rarely collected Cryptopone ochracea (Mayr, 1855) (Hymenoptera, Formicidae) in Hungary, we obtained the occurrence data with photos uploaded by non-professionals to the page of the largest Hungarian Facebook group dealing with ants a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…All of these species were classified as rare, with nine of them listed as globally threatened and one as Near Threatened. This underscores the significant role that volunteer observations can play in capturing data on rare and globally threatened species (Báthori et al, 2022; Fontaine et al, 2022; Tiralongo et al, 2020). Our study identified certain grid cells that had a larger contribution from the CS subset than from the RI subset, especially in the Northeast (Figure 3).…”
Section: Discussionmentioning
confidence: 86%
“…All of these species were classified as rare, with nine of them listed as globally threatened and one as Near Threatened. This underscores the significant role that volunteer observations can play in capturing data on rare and globally threatened species (Báthori et al, 2022; Fontaine et al, 2022; Tiralongo et al, 2020). Our study identified certain grid cells that had a larger contribution from the CS subset than from the RI subset, especially in the Northeast (Figure 3).…”
Section: Discussionmentioning
confidence: 86%